Towards a substantive knowledge-sharing model : exploring the systems dynamics between knowledge management, knowledge sharing and organisational ethos within a South African context - Van Aswegen, Berendien Susan (2012)
D.Phil. === In today's knowledge-intensive economy, an organisation's available knowledge is becoming an increasingly important strategic resource. The effective management of this resource is, consequently, one of the most important challenges facing today's organisation. Organisational learning processes which are responsible for the creation and sharing of knowledge should produce a core competence, which represents a form of valuable intellectual capital for the organisation and this has become a business imperative in the knowledgeintensive economy Without knowledge sharing between individuals, in groups, amongst groups and in the organisation as a whole there can be no knowledge and no sustainable competitive advantage through the use of organisational knowledge. Discovering the enablers and barriers to knowledge sharing is one of the aims of the study. I believe the proposed study could contribute to the "how" of knowledge sharing. This study will explore what the systemic relationship between knowledge management; knowledge sharing and organisational ethos is with the aim of developing a substantive knowledge-sharing model that explicates the knowledge-sharing processes. Based on the literature review, the reasons for organisations to focus on knowledge management and knowledge sharing are relatively consistent across organisations. At one level, organisations are concerned with keeping people informed regarding information and business processes to avoid duplication of effort, but also to stimulate collaboration and encourage group sharing. On a deeper level, most executives would agree that focusing on knowledge management is likely to increase organisational adaptability and competitiveness. Knowledge sharing can be viewed as a type of constant business innovation process.